IMPLEMENTASI ADAB MEMBACA DAN MENGHAFAL AL-QUR’AN TERHADAP SISWA DALAM PEMBENTUKAN KARAKTER QUR’ANI: (Studi Deskriptif di Sekolah Islam Qothrun Nada) - Umi Hasanah; Taufiq Fauzan Ginanjar (Berajah Journal, 2026)
In today's era, with the rapid development of technology and culture, while it has significantly contributed to the advancement of globalization, many have also become problems for the current generation. In this regard, the application of religious values is actually very helpful in increasing understanding in daily life. As Muslims, we should be concerned about this issue. Therefore, the purpose of this journal is to support the implementation of noble etiquette for students at Qothrun Nada Islamic School. Therefore, the title "Implementation of Etiquette for Reading and Memorizing the Qur'an and the Formation of Qur'anic Character in Students at Qothrun Nada Islamic School" was chosen, with an analytical study.This research is a field research study using qualitative methods, with data collection through interviews, observation, and documentation. The process of implementing the etiquette of memorizing the Qur'an is carried out over a week with activities such as ziyadah (adding new memorization) and muraja'ah (repetition). The method used for memorization is the Tasmi' method (listening and paying attention).